Dynamics and vibrational spectroscopy of quasi-one dimensional water wires inside carbon nanotubes of different diameter and chirality - Deepak Ojha; Peter Saalfrank (Scientific Reports)
Abstract Water strongly confined in nanostructures such as carbon nanotubes (CNTs) exhibits structural, dielectric, transport, dynamical and thermodynamical properties vastly different from bulk water, due to a strong modification of the (three-dimensional) hydrogen bond network. In this work, we mainly address the following aspects of extremely confined, quasi-one dimensional water chains in CNTs which have have not been emphasized much so far: The effect of chirality of the CNT, strong interactions with the hydrophobic walls and the (altered) vibrational response of confined water. Specifically, we have studied the (i) translation / diffusion, (ii) rotation / reorientation and (iii) vibrations of water chains confined within narrow carbon nanotubes (CNTs) with chirality indices (6,2), (6,4) and (6,6) using ab initio molecular dynamics. Special emphasis is on vibrational spectra, notably in the OH stretch region, obtained from fluctuations in the local OH stretching modes which were further employed to obtain two-dimensional infrared spectra and frequency-frequency correlation functions. We find that the vibrational distribution of water molecules under confinement is overall blue-shifted in comparison to bulk water, due to a breakdown of the three-dimensional hydrogen bond network. Further, the vibrational dynamics were found to dependent strongly upon the chirality and diameter of the CNTs, the latter causing stronger hydrophobic interactions with the walls of the nanotube. With respect to translational and rotational motion, the CNT-confined water molecules exhibit slower translational diffusion and faster reorientational motion compared to bulk liquid water for all cases simulated in this work.